Perancangan Standarisasi Depo di Departemen Yard Operation pada Perusahaan Ekspedisi Pelayaran - Yovita Rosalia; Tanti Octavia; Herri Christian Palit (Jurnal Titra, 2020)
This study aims to standardize the container yard at one of the shipping company. The company is currently going to expand their business by building a new container yard, but does not know the requirement of container yard area, facilities, and workers needed. The company once bought container yard area but the area is too big for their needs. The standardization made covers the number of conveyances, the number of container yard workers, the number of facilities along with the minimum size of the facility, container yard facility layout, and the minimum area of container yard. The method used in the design of the container yard standardization is related to the facilities layout and based on the company's current container yard situation. The results of this study indicate that the container yard standardization design is better viewed from the percentage reduction in moment layout in one of the container yard by 9.87%.